2018
DOI: 10.1016/j.jvs.2017.05.094
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial cell secretome as a novel treatment to prime adipose-derived stem cells for improved wound healing in diabetes

Abstract: HUVECs secrete protein factors that significantly increase proliferation and endothelial differentiation of ASCs under diabetic conditions. Injection of ischemic hindlimbs in diabetic mice with HUVEC-primed ASCs leads to enhanced angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…In contrast to the study of Merfeld-Clauss et al [ 9 ], the priming of hASCs with HUVEC secretome enhanced the proliferation, angiogenesis and wound healing abilities in a diabetic environment, created by the addition of glucose to the culture medium of both cell types, which suggests a strong paracrine effect unaffected by direct cell–cell contact [ 58 ]. In more detail, it was found that the priming significantly improved the proliferation of hASCs without additional fetal bovine serum in the HUVEC CM in comparison with a diabetic control.…”
Section: Asc—endothelium Crosstalkmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast to the study of Merfeld-Clauss et al [ 9 ], the priming of hASCs with HUVEC secretome enhanced the proliferation, angiogenesis and wound healing abilities in a diabetic environment, created by the addition of glucose to the culture medium of both cell types, which suggests a strong paracrine effect unaffected by direct cell–cell contact [ 58 ]. In more detail, it was found that the priming significantly improved the proliferation of hASCs without additional fetal bovine serum in the HUVEC CM in comparison with a diabetic control.…”
Section: Asc—endothelium Crosstalkmentioning
confidence: 80%
“…Endothelial differentiation is usually achieved by using a type of endothelial cell growth medium supplemented with growth factors and proteins, such as VEGF and IGF-1, that are known to be crucial for the differentiation process [ 4 , 35 , 53 , 54 ]. In addition, the endothelial cell secretome induces ASC differentiation [ 58 ]. Endothelial differentiation is detected by the presence of endothelial cell markers and biochemical processes, namely CD31, vWf, VEGF receptor 2 (VEGFR2), VEGFR1, vascular endothelial cadherin (VE-cadherin), endothelial cell nitric oxide synthase (eNOS) and acetylated low-density lipoprotein (ac-LDL) uptake [ 4 , 35 , 54 ].…”
Section: Adipose-derived Mesenchymal Stem/stromal Cellsmentioning
confidence: 99%
“…One of the examples of this approach can be co-culturing ADSCs (on advanced collagen wound matrix) with primary keratinocytes and keratinocyte conditioned medium, which after fifteen days initiated ADSCs differentiation towards keratinocytes (Edwards et al, 2018). Furthermore, ADSCs preconditioned by endothelial cell medium showed increased angiogenic potential, both in vivo (on diabetic mice model) and in vitro as well as enhanced proliferation and endothelial differentiation (Fromer et al, 2018). Similarly, human ADSCs co-cultured with endothelial cells on collagen peptide bioscaffold accelerated wound closure on irradiated mice model (Mashiko et al, 2018).…”
Section: Pretreatment and Co-culture Of Stem Cellsmentioning
confidence: 99%
“…12 Additionally, work performed at our institution has shown that in the diabetic setting, adipose-derived stem cells (ASCs) primed with HUVECconditioned medium (CM) increased cellular proliferation and viability to endothelial differentiation. 13 The purpose of our study was to investigate the effects of ASCs, endothelial cell-differentiated ASCs (EC/ASCs), and their associated CM on diabetic wound healing in a swine model. We hypothesized that ASC-based therapies would accelerate wound healing.…”
mentioning
confidence: 99%